Evaluation of mechanical and thermal properties of carrageenan/hydroxypropyl methyl cellulose hard capsule - Nur Amalina, Ramli; Fatmawati, Adam; Khairatun Najwa, Mohd Amin; Adibi, M. Nor; Ries, Michael E. (John Wiley & Sons, 2022)
The inherent source of gelatin used for commercial hard capsules causes a surging demand for vegetarian capsules. In this work, carrageenan is utilized in preparing hard capsules to meet consumer preferences. Hydroxypropyl methylcellulose (HPMC) was incorporated as a reinforcing agent to improve the low mechanical properties of hard capsules made of carrageenan. The HPMC concentration was manipulated from 0.2 to 1.0 w/v% in the carrageenan matrix. The increasing concentration of HPMC exerts significant effects on the tensile strength and elongation at break, with an improvement of 59.1% and 46.9%, respectively, at the optimized HPMC concentration of 0.8 w/v%. The loop strength of the capsule is also increased by 56.4% with decreasing moisture content. The downfield movement from around 3.20 ppm of the carrageenan proton to 3.33 ppm in the proton nuclear magnetic resonanance ( 1H-NMR) spectrum suggests the formation of intermolecular hydrogen bonding between carrageenan and HPMC, which correlates to the results of Fourier-transform infrared spectroscopy (FTIR) and zeta potential. The glass transition temperature of the film was increased from 37.8 to 65.3C, showing an upgrade in thermal stability. The film possesses a major mass loss with an activation energy of 64.7 kJ/mol with an increment of 43.4% compared to the control carrageenan. These findings support the conclusion that HPMC enhanced the mechanical properties and thermal stability of the carrageenan film, and the comprehensive analysis of the molecular interaction and decomposition kinetics subsequently may expand the application fields of the carrageenan-HPMC hard capsule as an alternative to gelatin in the future.